Management of immune-related myocarditis, myositis and myasthenia gravis (MMM) overlap syndrome: a single institution case series and literature review - Sánchez-Camacho, Alberto; Torres-Zurita, Alberto; Gallego-López, Laura; Hernández-Pacheco, Rocío; Silva-Romeiro, Silvia; Álamo de la Gala, María del Carmen; Peral-Gutiérrez de Ceballos, Enrique; de la Cruz-Merino, Luis (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized the treatment of various malignancies, particularly melanoma. However, immune-related adverse events (irAEs) pose significant challenges, particularly in cases of severe toxicity syndromes. One such life-threatening irAE is the myocarditis, myositis, and myasthenia gravis (MMM) overlap syndrome, which occurs in less than 1% of patients but has in-hospital mortality rates ranging from 40 to 60%. Due to its rarity and complexity, early recognition and a multidisciplinary approach are critical to improving outcomes.MethodsWe present a single-institution case series of four patients diagnosed with MMM overlap syndrome following ICI therapy. Clinical presentation, laboratory findings, imaging, and electrophysiological tests were analyzed to confirm the diagnosis. Therapeutic interventions-including corticosteroids, intravenous immunoglobulins (IVIG), plasma exchange (PLEX), tocilizumab, and rituximab- were evaluated in terms of efficacy and clinical outcomes.ResultsThe onset of MMM syndrome varied from 2 to 4 weeks after initiating ICI therapy. Patients presented with rapidly progressive symptoms, including ptosis, bulbar dysfunction, respiratory distress, myopathy, and cardiac conduction abnormalities. Immunosuppressive therapy with high-dose corticosteroids was initiated in all cases. Additional immunomodulatory treatments (IVIG, tocilizumab, PLEX, and rituximab) were administered based on clinical deterioration and autoimmune profile. Two patients achieved complete recovery, one remains on maintenance immunosuppression, and one died due to respiratory failure despite aggressive treatment.ConclusionMMM overlap syndrome is a severe and often fatal irAE associated with ICI therapy. Early identification, aggressive immunosuppressive treatment, and individualized therapeutic strategies are essential to optimize patient outcomes. Further research is needed to refine diagnostic criteria, identify predictive biomarkers, and establish standardized treatment protocols.